INTERGENERATIONAL CARE SUPPORT TRANSFER: INSIGHTS FROM THE GENERATION AND GENDER SURVEY - Mariana Buciuceanu-Vrabie; Ecaterina Grigoraș (Economy and Sociology, 2023)
Understanding intergenerational transfers of childcare is crucial in the context of declining birth rates, changing family structures, and population aging. Informal assistance in childcare is highly significant for many families with young children as it helps them balance their professional and parenting responsibilities. Existing research indicates that support provided by parents to their adult children in childcare positively impacts decisions regarding childbirth and women's participation in the labor market.